Incidence, severity and tolerability of pneumothorax following low‐dose CT‐guided lung biopsy in different severities of COPD. (4th October 2020) - Zhou, Mi; Wang, Ting; Wei, Dongshan; Zhu, Yong; Jiang, Yudan; Zuo, Cui; Jiang, Li; Chen, Hong; Guo, Shuliang; Yang, Li
Abstract: Background: The feasibility of pneumothorax following low‐dose CT‐guided puncture lung biopsy in different severities of COPD has not been reported. Methods: The data of the patients with pulmonary lesion who underwent low‐dose CT‐guided lung biopsy by one experienced operator in our hospital from January 1st to September 30th in 2019 were retrospectively collected. They were divided into COPD group and non‐COPD group. The risk factors, incidence and severity of pneumothorax with the severity of COPD and changes in MMRC score, treatment way and discharge time after pneumothorax were assessed. Results: Two hundred and nineteen patients were retrospectively enrolled in this study with 64 in the COPD group and 155 in the non‐COPD group. The average age, MMRC score and the incidence of pneumothorax after biopsy were significantly higher in the COPD group (64.7 ± 1.27 years, 1.02 ± 0.13, 31.3%) than in the non‐COPD group (58.8 ± 1.16 years, 0.35 ± 0.06, 17.4%, P  < 0.05). The incidence of pneumothorax between I‐II and III‐IV in COPD did not reach the significant difference ( P  = 0.863). COPD was the only independent risk factor for pneumothorax after biopsy in a multivariable regression ( P  < 0.05). MMRC score was significantly increased at post‐pneumothorax in the two groups ( P  < 0.001). There was no significant difference in diagnostic rate, severity of pneumothorax, the proportion of delayed pneumothorax, the changes in treatment way and discharge time between the two groups ( P  > 0.05). Conclusion: Although the incidence of pneumothorax after low dose CT‐guided lung biopsy is increased in COPD, there was no difference in the severity of pneumothorax amongst the different severities of COPD and it is well‐tolerated without increasing medical burden.